The Influence of Leadership and Work Discipline on Job Satisfaction of Employees at the Secretariat of the Regional House of Representatives (DPRD) of Makassar City - Risno, Trisnojaya; Natsir, Uhud Darmawan; Ruma, Zainal; Kurniawan, Agung Widhi; Burhanuddin, Burhanuddin (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the influence of leadership and work discipline on the job satisfaction of employees at the Secretariat of the Regional House of Representatives (DPRD) of Makassar City. The research adopts a quantitative approach with an associative design. The population consists of all civil servant employees (ASN) at the Secretariat, with a total sample of 75 respondents selected using a saturated sampling technique. Data were collected using questionnaires and analyzed through multiple linear regression with the help of SPSS version 26. The results show that leadership has a positive and significant effect on job satisfaction, while work discipline has a negative and significant effect on job satisfaction. Simultaneously, both leadership and work discipline have a significant influence on job satisfaction. Although the partial effects differ in direction (positive for leadership and negative for work discipline), together they significantly contribute to shaping the level of employee job satisfaction.